The Impact of CO2 Laser Treatment and Acidulated Phosphate Fluoride on Enamel Demineralization and Biofilm Formation - Loiola, Ana Bárbara Araújo; Aires, Carolina PatrÃcia; Curylofo-Zotti, Fabiana Almeida; Rodrigues Junior, Antônio Luiz; Souza-Gabriel, Aline Evangelista; Corona, Silmara Aparecida Milori (Journal of Lasers in Medical Sciences, 2019)
Introduction: This study evaluated the impact of CO2 laser treatment and acidulated phosphate fluoride (APF) on enamel demineralization and biofilm formation, using in vitro and in situ designs. Methods: Demineralized enamel slabs were distributed among 8 groups: placebo, placebo + continuous CO2 laser, placebo + repeated CO2 laser, placebo + ultrapulsed CO2 laser, 1.23% APF, APF + continuous CO2 laser, APF + repeated CO2 laser and APF + ultrapulsed CO2 laser. In the in vitro study, 15 enamel slabs from each group were subjected to a pH-cycling regimen for 14 days. In the cross over in situ design, 11 volunteers wore palatal appliances with demineralized enamel slabs for 2 periods of 14 days each. Drops of sucrose solution were dripped onto enamel slabs 8×/day. Biofilms formed on slabs were collected and the colony-forming units (CFU) of Streptococcus mutans and Lactobacillus were determined. Results: For both in vitro and in situ studies, there was no significant difference between treatments (P > 0.05). However, all treatments increased microhardness of demineralized enamel (P < 0.05). After a further in situ cariogenic challenge, with the exception of the placebo, all treatments maintained microhardness values (P < 0.05). Microbiological analysis showed no difference in Streptococcus mutans (P > 0.05) or Lactobacillus (P > 0.05) counts between groups. Conclusion: The results suggest that APF gel combined with the CO2 laser, regardless of the pulse emission mode used, was effective in controlling enamel demineralization, but none of the tested treatments was able to prevent bacterial colonization.